Comprehensive Review for Indium Recovery from Waste LCD Panels - 박재량; 박은덕 (에너지공학, 2023)
Waste liquid crystal display (LCD) accounts for one-sixth of the total global E-waste generated, a major environmental issue and a secondary resource for various metals and materials, including critical metals like Indium. The current review discusses and summarizes the recycling of waste LCDs and comprehensively focuses on indium recovery from waste LCD panels through various applied technologies. Extraction and recovery technologies employed for indium recovery from Indium-tin-oxide (ITO), which has 90 wt% In2O3 and 10 wt% SnO2, of the waste LCD panel is an important resource for indium has been discussed extensively. The extensive literature investigation indicates that indium recovery through various technologies like pyrometallurgy, chemical metallurgy, and hydrometallurgy have been employed. Among them, the hydrometallurgy process has been a major focus. Hence, various aspects like leaching, solvent extraction, and metal recovery through stripping of hydrometallurgy have been more intensively analyzed and discussed. The current review indicates that hydrometallurgy could be a promising technology for successful industrial-scale indium recovery from segregated panels of waste LCD. As most of the studies reported are on the laboratory scale, the requirement of industrial-scale investigation for process development is suggested.
Keywords: Indium; LCD; Recycling; Hydrometallurgy; Recovery